Electronic word of mouth dan minat beli pada follower produk hijab Naihijab.id - Nida Hasanati; Salsabila Elsya Sagfra (Cognicia, 2023)
The intense competition for selling hijab fashion in online shops makes businesses have to develop effective strategies so that their products can compete in the market. One strategy used to attract consumer buyers is to introduce their products through electronic word of mouth (eWom). This study aims to test eWom's ability to predict consumer buying interest. The subjects of this study were 361 followers of the Naihijab.id tiktok account, aged 17-24 years, which were obtained using the accidental sampling technique. The scale used is the EWOM scale and the purchase intention scale. A simple linear regression test results show that the hypothesis is accepted. Namely, eWom can predict buying interest in followers of the Naihijab. id tiktok account by 21.5%. Of the seven dimensions of eWOM, only four significantly predict purchase intention: platform assistance, positive self-enhancement, social benefits, and advice seeking. In contrast, the remaining three dimensions are insignificant in predicting purchase intention. The implications of this research show that for consumer buying interest to increase, Naihijab.id business owners need to strengthen several aspects of eWom that have a strong contribution to consumers and improve several aspects that are not significant. Keywords: Buying intention, electronic word of mouth, onlineshop